Spatial model of forest area utilization in integration of production forest functions, Central Sulawesi, Indonesia - Akhbar, Akhbar; Naharuddin, Naharuddin; Arianingsih, Ida; Misrah, Misrah; Akhbar, Rahmat Kurniadi (Agriculture and Natural Resources, 2024)
Importance of the work: The determination of the function of limited and permanent production forests has different land- and climate-limiting factors. Therefore, environmental damage is feared when using integrated production forest areas as stipulated in a Government Regulation of the Republic of Indonesia. Objectives: To identify models applicable to dryland ecosystems for the utilization of forest areas in the spatial integration of producing good functions. Materials & Methods: A limited production forest study area covering 500.28 ha was investigated using a descriptive method with a spatial data simulation approach utilizing GIS technology. Results: The spatial models of forest area utilization in the integration of forest functions were: Model 1 (local protected area); Model 2 (utilization of timber forest products in a natural forest with delayed selective logging); Model 3 (utilization of timber forest products in a natural forest with selective logging); Model 4 (reforestation/plantation forest pattern rehabilitation); and Model 5 (rehabilitation of agroforestry patterns), with areas of 374.48 ha, 74.59 ha, 0.35 ha, 50.11 ha, and 0.75 ha, respectively. Main finding: The delineation of the five spatial models of forest area utilization in the integration of production forest functions needs to be followed up with testing at the site level.